Health professions students’ interprofessional experiences on a rural learning platform - Joubert, A.; Botha, R. W.; Morgan, H.; Wilmot, M.; Hagemeister, D. T. (South African Journal of Higher Education, 2020)
HEALTH PROFESSIONS STUDENTS’ LEARNING EXPERIENCES ON A RURAL COLLABORATIVE LEARNING PLATFORM ABSTRACT A Faculty of Health Sciences launched a rural collaborative learning platform to cultivate interprofessional key competencies and to improve health outcomes. The purpose of the study was to describe health sciences students’ experiences of an rural collaborative learning platform. Health professions students created digital stories reflecting on their collaborative learning experiences. Purposive sampling resulted in 23 submissions. Qualitative analysis of content identified themes and categories. Three themes, namely, metaphor, critical consciousness and professional socialisation, were identified. The metaphor categories, Journey, Setting world ablaze, Water, and Puzzle, represent students’ desire to use visual cues to describe their experiences. Transformation, Personal development and Empathy signified critical consciousness. Collaborative practice, Values, Reflective practice, and Key competencies relate to professional socialisation. The researchers gained understanding of students’ experiences on an rural collaborative learning platform. Through digital stories, students became aware of professional interdependency, which linked their experiences to key interprofessional competencies.